Empowerment and Effectiveness of School Committees in Tanzania - Masue, Orest Sebastian (University of Bergen, 2025)
A thesis submitted to the Department of Administration and Organisation Theory University of Bergen, Norway in partial fulfilment of the requirements for the degree of Master of Philosophy in Public Administration.